PENGARUH EDUKASI BERBASIS FAMILY CENTERED MATERNITY CARE TERHADAP PEMBERIAN ASI DALAM UPAYA PENCEGAHAN STUNTING - Chainny Rhamawan; Rentawati Purba (Jurnal Ilmiah Kebidanan Imelda, 2026)
Background: Stunting remains a major public health issue in Indonesia, strongly associated with inadequate nutrition during the early stages of life. Exclusive breastfeeding is recognized as one of the most effective interventions to prevent stunting. However, breastfeeding practices are influenced by maternal knowledge, attitudes, and family support. The Family Centered Maternity Care (FCMC) approach emphasizes family involvement in maternal and child health, aiming to improve breastfeeding practices and child nutrition. Objective: This study aimed to analyze the effect of FCMC-based education on breastfeeding practices and mothers’ perceptions of fulfilling children’s nutritional needs as an effort to prevent stunting. Methods: A mixed-method design was applied, combining quantitative and qualitative approaches. The quantitative phase used a randomized controlled trial involving 100 postpartum mothers divided into intervention and control groups. The intervention group received FCMC-based education, while the control group did not. Data were collected using structured questionnaires on breastfeeding practices, knowledge, attitudes, and family support, complemented by semi-structured interviews. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were thematically analyzed. Results: The majority of respondents were <18 years old, had basic education, and 65% were employed. Most mothers had good knowledge (59%), good attitudes (61%), and adequate family support (54%). Breastfeeding was reported by 68% of participants. Statistical analysis showed that mothers in the intervention group were almost four times more likely to have a good perception of fulfilling child nutrition compared to the control group (OR = 3.881; 95% CI: 1.561–9.650; p = 0.005). Qualitative findings highlighted the role of family involvement, especially from husbands, in supporting breastfeeding practices. Conclusion: FCMC-based education significantly improves mothers’ perceptions of child nutrition and enhances breastfeeding practices. Integrating FCMC into maternal health programs is recommended as a sustainable strategy to support exclusive breastfeeding and prevent stunting in Indonesia.